Do not question my honour: A social-scientific reading of the parable of the minas (Lk 19:12b–24, 27) - Eck, Ernest van (HTS teologiese studies, 2011)
This article attempted to read the parable of the minas in a 30 CE context, employing a social scientific reading. The integrity of the parable was delimited to Luke 19:12b–24 and 27. It was argued that this version of the parable (that stems from Q) goes back to the earliest layer of the historical Jesus tradition and is a realistic version of the historical background, political background and socioeconomic background of 30 CE Palestine. In this reading of the parable, attention was given to an aspect much neglected in previous scholarship regarding the interpretation of the parable, namely that the third slave in the parable is not condemned. It was argued that this neglected aspect is important for the strategy of the parable. The reading concluded that the parable has two foci; it shows how, in the time of Jesus, the elite exploited the nonelite and how to protest in a situation where the peasantry (the exploited) had no legitimate way of protesting against the exploitative practices of the elite.